Autecology of Drosera burmanni in the Wolobobo Botanic Gardens, Ngada District, Flores Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Witono JR, Usmadi D, Wihermanto, Purnomo DW, Safarinanugraha D, Pakiding Y, Netoseso N. 2020. Autecology of Drosera burmanni in the Wolobobo Botanic Gardens, Ngada District, Flores Island, Indonesia. Biodiversitas 21: 2137-2145. Drosera burmanni Vahl is a native carnivorous plant from tropical and subtropical Asia to the West Pacific, including Flores Island. During the botanical survey, a small population of the species was found in a limited area in the Wolobobo Botanic Gardens, Flores Island. Conservation of the species is necessary, since the habitat might be developed for the botanic gardens infrastructure. This research aims to study the autecology of D. burmanni, including environmental preferences and its associated species. Thirty plots with 2 x 2 m each were made to recognize its associated species and the pattern of its population distribution and its soil requirements. In the Wolobobo Botanic Gardens, D. burmanni flourishes with an average annual rainfall of 1835 mm; a temperature of 12.50-26.2° C; 48-99% humidity; at an altitude of 1489-1491 m asl.; a soil pH of 6.66, which contains very high C-organic, a high C/N ratio, moderate N total, K2O, P2O5, low CEC, and very low K, Na, Ca, Mg, and BS. Drosera burmanni displays a density of 8.5 individuals per m2 and is associated with 20 species, which belong to 19 genera and 9 families. The species has a clustering pattern and a positive association with Erigeron sumatrensis, Spinifex littoreus, and Imperata cylindrica. To conserve D. burmanni in the Wolobobo Botanic Gardens, it is necessary to designate its natural habitat as an in situ conservation area.
Keywords: Associated species, carnivorous plant, climatic and soil requirements, distribution pattern, in situ conservation